Hematopoietic Developmental Potential of Human Pluripotent Stem Cell Lines Is Accompanied by the Morphology of Embryoid Bodies and the Expression of Endodermal and Hematopoietic Markers - Tesarova, Lenka; Simara, Pavel; Stejskal, Stanislav; Koutna, Irena (Cellular reprogramming, 2017)
The potential clinical applications of hematopoietic stem cells (HSCs) derived from human pluripotent stem cells (hPSCs) are limited by the difficulty of recapitulating embryoid hematopoiesis and by the unknown differentiation potential of hPSC lines. To evaluate their hematopoietic developmental potential, available hPSC lines were differentiated by an embryoid body (EB) suspension culture in serum-free medium supplemented with three different cytokine mixes (CMs). The hPSC differentiation status was investigated by the flow cytometry expression profiles of cell surface molecules, and the gene expression of pluripotency and differentiation markers over time was evaluated by real-time reverse transcription polymerase chain reaction (qRT-PCR). hPSC lines differed in several aspects of the differentiation process, including the absolute yield of hematopoietic progenitors, the proportion of hematopoietic progenitor populations, and the effect of various CMs. The ability to generate hematopoietic progenitors was then associated with the morphology of the developing EBs, the expression of the endodermal markers AFP and SOX17, and the hematopoietic transcription factor RUNX1. These findings deepen the knowledge about the hematopoietic propensity of hPSCs and identify its variability as an aspect that must be taken into account before the usage of hPSC-derived HSCs in downstream applications.
Keywords: cytokines; Antigens, Differentiation; pluripotent stem cells; Cell Line; lidské embryonální kmenové buňky; Gene Expression Regulation; hematopoietic stem cells; hematopoéza; Embryoid Bodies; regulace genové exprese; diferenciační antigeny; Humans; embryoidní tělíska; embryoid bodies; endoderm; Human Embryonic Stem Cells; hematopoietic differentiation; buněčné linie; Hematopoiesis; Endoderm; lidé